A Farmer's Alliance: The Joint Stock Companies of the Home District and the Economic Roots of Deliberative Democracy in Upper Canada - Schrauwers, Albert (Ontario History, 2007)
This article addresses the economic roots of the fight for democratic reform in Upper Canada, and the role of a small religious sect, the Children of Peace, in particular. The Children of Peace were critical players in a number of “joint stock companies” such as the Farmers’ Store House (a co-operative farm produce marketing company) and the Bank of the People. Joint stock companies lacked a charter or limited liability for their shareholders, and this made them models of “responsible government.” These companies, and their directors, helped found the democratic reform political union, the Canadian Alliance Society, and build its meeting place “Shepard’s Hall.”